Cognitive Bias Mitigation : How to make business decision-making more rational? - Kučera, Tomáš (2016)
The thesis is concerned with cognitive biases, especially with confirmation bias, and with various approaches to their mitigation. It elaborates on three main categories of debiasing strategies, namely increasing incentives, adjusting the environment in order to avoid or offset the bias, and training people in recognizing the situations in which a bias occurs and in mitigating the effects of the bias. An experiment in which the patterns of information selection and the effects of a debiasing training were investigated is reported. The results show that participants exhibited confirmation bias both in the selection of information and in the information processing, and that debiasing training effectively decreased the level of confirmation bias by 33 % at the 5% significance level. The debiasing training took the form of a short video which included information about confirmation bias and its impact on judgement, and mitigation strategies.